Structural equation modelling and numerical simulation on the entire process of e-commerce model. (26th November 2021) - Fu, Xiaoxi; Sun, Xuecheng; Li, Wentao; Roger, Mark
Nowadays, most enterprises introduce e-commerce to enhance efficiency, broaden the market and restructure their organisation. Therefore, many scholars have taken notice on how to introduce and implement e-commerce model in traditional enterprises successfully. This study tried to explore the complex relationship between original enterprise operation and e-commerce model using numerical simulation. Through the simulation of the entire process of e-commerce mode introduction and implementation, we found that traditional operation could promote the implementation of e-commerce at initial phase. With the implementation of the e-commerce model, the original operational base will become an obstacle. To cope with this, companies need to break the inherent boundaries and industry concepts and simplify the organisational structure to promote the full utility of e-commerce model.